(untitled) (Revista Contexto & Educação, 2026)
This study presents a systematic review of the literature on Potentially Meaninfull Teaching Units (PMTU) in the context of Science teaching. Based on Ausubel’s Theory of Meaningful Learning, PSTUs are didactic sequences organized to integrate students’ prior knowledge with new knowledge, promoting deeper and more contextualized learning. The research analyzed dissertations, theses and articles published in Brazilian databases, resulting in the selection of 17 works. The results revealed that the application of PMTU is predominant in the final years of Elementary School and High School, with an emphasis on topics such as Ecology, sustainability and the human body. The studies indicated that PMTU has advanced in the development of critical and cognitive skills, in addition to favoring a more meaningful pedagogical practice. Despite its proven potential, there is a need for greater flexibility of the original model, as well as its adaptation to other levels of education and greater integration with educational technologies. It is concluded that PMTU represents an innovative and effective strategy for teaching Science, with the capacity to transform traditional practices and promote student engagement in the learning process.